Evaluation of role of Jasminum sambac against ulcerative colitis in rats (Indian Journal of Traditional Knowledge (IJTK), 2023)
Current investigation is designed to find out the role of Jasminum sambac (JS) against Acetic Acid (AA)-induced ulcerative colitis in rats. 30 male albino Wistar rats were randomly separated into 5 batches (n=6): normal: admitted with distilled water for 7 days; negative: received the distilled water for 1- 3 days and from 4-7 days received the 2 mL of AA (4% v/v) rectally; test 1, 2 and standard group: orally received the ethanolic extract of leaves of Jasminum sambac (EEJS) at doses 250, 500 mg/kg and prednisolone 2 mg/kg from 1-3 days without AA and from 4-7 days received the 2 mL of 4% v/v AA rectally after 2 h administration of EEJS and prednisolone. On 8th day rats were sacrificed and colon tissues were examined. Rats with acetic acid-induced colitis exhibited significant decrease in body weight, colon length, superoxide dismutase, catalase, reduced glutathione, significant rise in colon weight, oedema, disease activity index, macroscopic damage score, occult blood in stool, stool consistency and lipid peroxidation. Pre-treatment with EEJS at doses 250, 500 mg/kg orally significantly regularized the above-mentioned parameters in dose dependent manner. Ethanolic extract of Jasminum sambac could protect the AA-produced ulcerative colitis by attenuation of macroscopic damage, microscopic damage, and oxidative biomarkers.